ADOPTING HOTS FOR LANGUAGE LEARNING: A CASE OF ARABIC - Ulum, Miftahul; Huda, Mokhammad Miftakhul (International Journal of Psychosocial Rehabilitation, 2020)
Learning Arabic in Excellent Senior High School of Darul Ulum Step 2 has used the 2013 Curriculum but in practice the teacher has not taught much with the HOTS method, especially Arabic subjects. Therefore, it is deemed necessary to teach Arabic with the HOTS approach, it is expected that students will not only answer at the C-1 (knowing), C-2 (understanding), and C-3 (applying) levels related to Arabic subject themes, but students are also required to develop at the level of C-4 (synthesis / analysis), C-5 (evaluation), and C-6 (creative). Achievements in this study are to explain the HOTS (High Order Thinking Skills) system and its relation to Arabic Literacy in senior high school and measure the implications of the innovations in the development of HOTS (High Order Thinking Skills) towards the development of innovative learning. In this study, researchers used several approaches that were appropriate for their research. The approach is a descriptive approach, analytical approach, and critical approach. The results achieved in this study were the Innovation of the development of Arabic learning based on HOTS (High Order Thinking Skills) developed in this study covering several stages, namely Basic Competency Analysis (KD), Indicator Analysis, Analysis of student characteristics, Formulating learning objectives, Analysis material, Developing strategies and learning activities, developing learning tools, Developing assessments, and linking them to HOTS principles, and Revising all aspects and steps of learning development. The results of the development of Arabic learning innovations in Excellent Senior High School Of Darul Ulum Step 2 by using the HOTS model developed in this research are learning device products that include lesson plans, teaching materials, and learning assessments designed on the basis of HOTS (High Order Thinking Skills).